Abuse suffered by parricides in childhood - Teche, Ana Maria Freitas; Gomide, Paula Inez Cunha (Psicologia Argumento, 2019)
The purpose of this study was to identify parenting education practices and physical, psychological and sexual maltreatment endured by parricides committed to prisons and Civil Police Stations of the state of Paraná. Two patricides and one matricide individuals participated in the research, all male, aged 27, 39 and 42 years old. Two instruments were used to gather data: a structured interview and PSI - Parenting Style Inventory (Gomide, 2006). The data wered presented as Case Studies. Later similarity analyses on maltreatment history were performed. Parenting style indexes received risk scores. All parricides had a childhood marked by physical and emotional maltreatment and negligence, being that two of them reported sexual abuse in childhood. This study emphasizes the need of studying intervention options and trveatments aimed at the social reintegration of the parricide.